Attitudinal factors of Librarians in-charge influencing the School Library and Learning Resource Centres to be effective - Santhalingam, R.; Sinnathamby, K.; Chandrasekar, K. (Sri Lanka Library Association, 2019)
School Library and Learning Resource Centres (SLLRCs) are expected to comprise information resources necessary for the educational activities and maintain close relationship with classroom teaching. Besides, attitudes of Librarians in-charge largely contribute in organizing and administering SLLRCs, guiding students towards resource-based learning and encouraging them for self-directed learning. This study intended to assess the attitude of Librarians in-charge in relation to the development of SLLRCs. The study conducted in the schools attached to the Kopay Educational Division of the Jaffna Zone. Except Type 111 schools (n=17, with reading corners at classrooms), all categories (1AB=5, 1C=3, Type 11=15) were selected for the study. A questionnaire distributed among Librarians in-charge of the selected schools, in order to get their opinion regarding library infrastructure, library organization, library usage, support from school community in library development, and their professional competency. Additional information collected via interviews with Librarians in-charge. The data collected were statistically analyzed and reported. Results revealed that 61% of the schools have separate building for the library. However, 26% of these libraries are functioning with inadequate basic facilities. Further, 86% of the Librarians in-charge are not satisfied with the existing infrastructure facilities of the SLLRCs. More than 50% of the Librarians in-charge are satisfied with the library organization. Even though, library usage of students (64%) and staff (54%) are at satisfactory level, reading promotion activities (e. g. readers circle, reading camps) are lacking, according to Librarians in-charge. Besides, Librarians in-charge perceived that support from school principals (54%), students (45%) and teachers (41%) in the development of SLLRCs is comparatively greater than the contribution of Old Students Unions (23%). Regarding library personnel, only 54% of the Librarians in-charge have professional qualification in Library and Information Science, though, 36% of them have skills related to cataloguing, classification and library automation. Whereas, 64% of the Librarians in-charge claimed that they are performing the library duties with satisfaction. This study concludes that Librarians in-charge are not interested in acquiring professional qualification related to library science, due to lack of promotional opportunities and recognition for the profession. Furthermore, they pointed out the shortcomings in providing infrastructure facilities and insufficient physical resources at SLLRCs, and lack of support for reading promotion activities among students.
Keywords: School Library and Learning Resource Centres; School libraries; Librarians in-charge; Teacher Librarian